Optimization model of mining operation scheduling for underground metal mines - LI Guo-qing; LI Bao; HU Nai-lian; HOU Jie; XIU Guo-lin (工程科学学报)
To realize the accurate and scientific optimization of mining production scheduling for underground metal mines, a mathematic model based on 0-1 integer programming was constructed in view of the characteristics of mining process, such as decentralized production sites, complex production organization and difficulty in controlling the quality of the ore. After the requirements of economic index and spatial sequence relationship being analyzed, an optimization model was proposed which constrained by the yield balance, ore-drawing capacity and combination of high and low grade, aiming at the minimum grade deviation. The optimal mining schedule for underground mines was obtained by computer technology and integer programming to meet the operating procedure, mining sequence, production capacity and other factors. The optimization model was verified by a case in a large gold mine. The optimal solution, expressed by the Gantt chart, indicates that the model is not only meaningful to guide the completion of production tasks in underground mine operation scheduling, but also meets the requirements of continuity and equilibrium of operation scheduling.